Fast decodable MIDO codes from crossed product algebras - Oggier, Frederique (2010)
The goal of this paper is to design fast-decodable space-time codes for four transmit and two receive antennas. The previous attempts to build such codes have resulted in codes that are not full rank and hence cannot provide full diversity or high coding gains. Extensive work carried out on division algebras indicates that in order to get, not only non-zero but perhaps even non-vanishing determinants (NVD) one should look at division algebras and their orders. To further aid the decoding, we will build our codes so that they consist of four generalized Alamouti blocks which allows decoding with reduced complexity. As far as we know, the resulting codes are the first having both reduced decoding complexity, and at the same time allowing one to give a proof of the NVD property.